Effect of drying and storage conditions on the quality of natural and washed coffee - Coradi, Paulo Carteri; Borém, Flávio Meira; Saath, Reni; Marques, Elizabeth Rosemeire (Coffee Science - ISSN 1984-3909)
The objective of the work was to evaluate alterations in the quality of natural and washed coffee under different drying conditions (coffee drying yard, temperature of 40ºC and 60ºC) and storage conditions at 60% of relative humidity, with controlled temperature of 23ºC, at 90 and 180 days. The work was carried out in the Engineering Department and in the Coffee Post-Harvest Technology Pole of the Federal University of Lavras. The manual harvest of the coffee (Coffea arabica L.), Topázio variety, was selective. Part of the coffee was pulped and the other part was processed in the natural form. A portion of each type of coffee was submitted to drying on the yard and two other samples were processed in a mechanical dryer, at temperatures of 40ºC and 60ºC. After drying, the coffee was stored in an air-tight room, in which a stable relative humidity of 60% was maintained with a solution of magnesium nitrate. Quality evaluation, sensorial analyses, electric conductivity and potassium leaching tests, total titrable acidity, fatty acidity and total and reducing sugars determinations were carried out. The results showed that the coffee dried at 60ºC, after 90 days storage, presented the poorest quality. The physical-chemical evaluations of the drying and storage conditions showed that washed coffee presents better quality when compared to the product in its natural form.